Factors associated with infection and mortality in neonates following abdominal surgery - Brigitta R. V. C. Corebima; Eko Sulistijono; Widanto Widanto; Cheah Fook Choe (Indonesian Pediatric Society, 2023)
Background The outcomes of neonatal surgical cases has steadily improved in the last decade. However, limited local data are available in Indonesia regarding the contributing factors and outcomes of surgical procedures in neonates. Objective To determine the incidence of infection and mortality in neonatal surgical cases in Saiful Anwar Hospital, Malang, East Java, Indonesia. Methods This retrospective cohort study included neonates who underwent abdominal surgery over a period of 20 months from January 2021 to August 2022. Data collected included subjects’ basic demographics, primary surgical diagnoses, associated congenital anomalies, pre-operative conditions, and referral status. These parameters were analyzed in relation to the incidence of infection and mortality in the 30 days after surgical procedure. Results Of fifty-four neonates in this study, the most common neonatal surgical conditions were anorectal malformation, followed by necrotizing enterocolitis and Hirschsprung’s disease. The mortality rate at 30 days was 48%. The most common associated factors were sepsis (OR 0.778; 95%CI 0.233 to -1.167; P=0.041), pre-operative respiratory failure/hemodynamic instability (OR 2.129; 95%CI 1.039 to 3.126; P<0.001), and delayed referral (OR 0.295; 95%CI 0.074 to 1.177; P=0.048). Other factors such as age at presentation, gender, gestational age, birth weight, referral patient vs. those born in our hospital, associated congenital anomalies, and emergency procedures were not associated with mortality. The survival time in the sepsis group [17.30 (1.68-13.98) days] was significantly lower than in the non-sepsis group [25.95 (1.63-22.76) days] (P< 0.001). Conclusion Sepsis, pre-operative respiratory failure/hemodynamic instability, and delayed referral are risk factors for mortality in neonates following abdominal surgery. Identification of these risk factors and early intervention are important to improve outcomes.